Prolonged pituitary down-regulation with full-dose of gonadotropin-releasing hormone agonist in different menstrual cycles: a retrospective cohort study - Ying,Yingfen; Yang,Tanchu; Zhang,Huina; Liu,Chang; Zhao,Junzhao (PeerJ, 2019)
Background The efficiency of prolonged down-regulation caused by a full-dose of gonadotropin-releasing hormone agonist (GnRH-a) injected during different menstrual phases has not yet been researched. Our goal was to evaluate the effects of GnRH-a, which was used in different phases of the menstrual cycle in patients undergoing in vitro fertilization and embryo transfer. Methods This was a retrospective cohort study. A total of 320 patients received a prolonged pituitary down-regulated full-dose (3.75 mg) of triptorelin in the early follicular phase, and 160 patients received the same full-dose of triptorelin during the mid-luteal phase. Clinical and laboratory outcomes were compared between the two groups. Results The basic characteristics of the two groups were comparable. The mean number of retrieved oocytes, fertilized oocytes, cleavage oocytes and good quality embryos were comparable between the two groups. Although there was a higher antral follicle count, cyst formation rate, fertilization rate and cleavage rate in the follicular phase group, no statistically significant effects were seen on implantation rate (41.15% vs. 45.91%), clinical pregnancy rate (60.38% vs. 61.36%), ongoing pregnancy rate (57.74% vs. 57.58%), live birth rate (56.23% vs. 57.58%) or early abortion rate (2.64% vs. 3.79%) per fresh transfer cycle. Moreover, severe ovarian hyperstimulation syndrome rates at the early stage (1.89% vs. 2.27%) were low in both groups. Conclusions Prolonged pituitary down-regulation achieved by utilizing a full-dose of GnRH-a administrated in either phase of the menstrual cycle can have a positive effect on ongoing pregnancy rate and live-birth rate per fresh embryo transfer cycle. Ovarian cyst formation rate was higher in the follicular phase group, but this did not have any adverse impact on clinical results.
Keywords: In vitro fertilization and embryo transfer; Gonadotropin-releasing hormone agonist; Pituitary down-regulation; Controlled ovarian hyperstimulation (COH); Ovarian cyst